The Role of Source‐Sink Dynamics in the Assessment of Risk to Nontarget Arthropods from the Use of Plant Protection Products. (27th August 2021) - Lewis, Gavin; Dinter, Axel; Elston, Charlotte; Marx, Michael Thomas; Mayer, Christoph Julian; Neumann, Paul; Pilling, Ed; Braaker, Sonja
Abstract: The concept of source‐sink dynamics as a potentially important component of metapopulation dynamics was introduced in the 1980s. The objective of the present review was to review the considerable body of work that has been developed, to consider its theoretical implications as well as to understand how source‐sink dynamics may manifest under field conditions in the specific case of nontarget arthropods in the agricultural environment. Our review concludes that metapopulation dynamics based on field observations are often far more complex than existing theoretical source‐sink models would indicate, because they are dependent on numerous population processes and influencing factors. The difficulty in identifying and measuring these factors likely explains why empirical studies assessing source‐sink dynamics are scarce. Furthermore, we highlight the importance of considering the spatial and temporal heterogeneity of agricultural landscapes when assessing the population dynamics of nontarget arthropods in the context of the risk from the use of plant protection products. A need is identified to further develop and thoroughly validate predictive population models, which can incorporate all factors relevant to a specific system. Once reliable predictive models for a number of representative nontarget arthropod species are available, they could provide a meaningful tool for refined risk evaluations (higher tier level risk assessment), addressing specific concerns identified at the initial evaluation stages (lower tier level risk assessment). Environ Toxicol Chem 2021;40:2667–2679. © 2021 ERM, FMC, Syngenta, Bayer AG, BASF SE, Corteva agriscience. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.